Exploration of fluorescence behavior of an imidazolium-based chemosensor in solution and in the solid state and its turn-on response to Al3+ in pure aqueous medium. Issue 7 (6th May 2020) - Saini, Vaishali; Krishnan, Rangan; Khungar, Bharti
Abstract : An imidazolium-based quinoline framework is constructed, and its fluorescence behaviour studies with fluorescence turn-on chemosensory response to the selective detection of Al 3+ in aqueous medium are discussed in detail. Abstract : An imidazolium-based quinoline Schiff base ImSB was developed and fully characterized by FT-IR, 1 H and 13 C NMR spectroscopy, mass spectrometry, and X-ray crystallography. The fluorescence behaviour of ImSB in solution and in the solid state, keto–enol stability at different concentrations and pH in aqueous medium were investigated. The UV-visible and fluorescence studies were performed to determine the response of ImSB towards different ions in aqueous medium. ImSB showed a turn-on fluorescence behaviour with high selectivity towards Al 3+ over various cations and anions due to chelation-enhanced fluorescence (CHEF), inhibition of photoinduced electron transfer (PET) and restriction of CN isomerization. The low detection limit for Al 3+ was 54 nM and Job's plot confirmed 1 : 1 stoichiometry between ImSB and Al 3+ with a high binding constant value of 4.16 × 10 6 M −1 . Monitoring of Al 3+ was also demonstrated in real water samples (mineral, river and tap water). The structural and electronic parameters of ImSB and ImSB -Al 3+ were also studied theoretically.